Pengembangan Aplikasi Kasir pada Sistem Informasi Rumah Makan Mie Happy - Calisto, Calvin; Narulita, Siska (UNIVERSITAS STEKOM, 2024)
In the current era of information technology, easy and efficient transaction management is an important requirement in the business world, both small and large scale. Rumah Makan Mie Happy is a medium-scale culinary business. Happy Noodle Restaurant provides noodle-based preparations. In its daily life, Happy Noodle Restaurant can serve around 100 consumers, so that the service process requires speed to serve consumers. But in fact, Mie Happy Restaurant still uses manual data processing and transaction management, so it often experiences problems such as slow payment processes, frequent loss of receipts or proof of payment, difficulty in recapitulating or reporting transactions both daily and monthly, and frequent errors in the calculation process. From the problems experienced by Mie Happy Restaurant, the author is interested in developing a web-based cashier application that can help in all matters related to transaction management at Mie Happy Restaurant. The research conducted aims to build or develop a cashier application for Happy Noodle Restaurant that can improve the efficiency and effectiveness of transaction management. This cashier application was built or developed using Hypertext Markup Language (HTML) and Hypertext Preprocessor (PHP) with Visual Studio Code editor and MySQL Database Management System (DBMS). The results of testing with black box testing show that the cashier application developed in functionality has run as expected. This web-based cashier application provides convenience for admins and increases the effectiveness and efficiency of operational activities.